Health risk assessment for occupants as a decision-making tool to quantify the environmental effects of particulate matter in construction projects. (15th August 2019) - Jung, Seunghoon; Kang, Hyuna; Sung, Seulki; Hong, Taehoon
Abstract: With the seriousness of the environmental impact of air pollutants, it is necessary to predict the PM10 emissions and quantify its health risks in construction projects to prevent conflicts with occupants. Therefore, this study aimed to propose a method for assessing the health risks of PM10 for occupants in the area near the construction sites as a decision-making tool. Toward this end, PM10 concentration and health risks for the occupants near the construction site were estimated. The results of the case study show that there is a difference in PM10 concentration among areas in the different distances (i.e., 31.5 times at maximum) and directions (i.e., 4.2 times at maximum) from the construction site due to wind direction and terrain obstacles. Personal health risk of PM10 for occupants was higher in the school by 35.3% than in the apartment complex due to their higher proportion of population exposed to PM10 during the construction. Meanwhile, total population group health risk was higher for the apartment complex than the school by 63.2% due to their more population. The proposed method for health risk assessment of PM10 for occupants could be helpful as a decision-making tool for a construction company and occupants, while diminishing social costs by civil complaints and increasing productivity of the construction project. Highlights: The environmental effect of PM10 in construction projects is quantified. PM10 concentration in the area near the construction site was estimated. Health risks for the occupants were assessed according to the building type and area. Personal health risks were higher in schools than in apartment complexes. Population group health risks were higher in apartment complexes than in schools.